Lived experiences of domestic violence among Minangkabau women: A phenomenological study - Yanti Puspita Sari; Khatijah Lim Abdullah; Hermalinda Hermalinda (Jurnal Keperawatan Padjadjaran, 2025)
Objective: This study aimed to explore the lived experiences of women who have faced domestic violence, focusing on the causes of the violence, its impact on their health, and the decision-making processes they undertook in response. Method: This study used a phenomenological study approach. The inclusion criteria were women from the Minangkabau tribe, aged 18-40, married or previously married, and with children. Participant recruitment was conducted through the Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak/ Integrated Service Center for the Empowerment of Women and Children) and the Women’s Crisis Center (WCC) “Nurani Perempuan”, based on predetermined inclusion criteria. Data collection continued until thematic saturation was reached. Nine women were involved. In-depth interviews and field notes were transcribed verbatim, and theme analysis was performed using the seven-step Collaizzi technique. Results: Four themes emerged from the data: (1) failure to resolve family conflict; (2) physical and psychological despair; (3) inability to make decisions; (4) need for external support. Participants’ experiences reflect the erosion of traditional protective systems due to cultural shifts, economic dependence, and societal pressures. Conclusions: The study highlights that unresolved family conflict, poor health outcomes, and limited decision-making power shape women's vulnerability to domestic violence. Strengthening community-based support and culturally sensitive interventions is recommended to empower women and reduce the risk of domestic violence.